IS WOMEN'S LABOUR FORCE PARTICIPATION POTENTIALLY ENHANCED BY DIGITAL FINANCIAL INCLUSION? EVIDENCE FROM AFRICA - Benedict Azu; Taiwo Queen Adjeke; Agbobu Shedrack Onyeka (International Studies Journal)
This research delves into the correlation between women's labour force participation and digital financial inclusion, while also elucidating the obstacles that impede women's access to digital finance. Our database is derived from the Global Findex database, 2021 edition, and we have mobilised a microeconomic database covering 14,281 African women. based on polls conducted in 29 African nations that are nationally representative. The empirical findings are analysed using the Probit model estimate methodology. According to our research, women's engagement in the labour market is favourably correlated with financial inclusion through digital channels more so than through traditional ones. It was discovered that formal financial services channels had a major and advantageous effect on women's labour market involvement. According to our research, women encounter a number of barriers when attempting to obtain financial services via digital and traditional channels. Non-voluntary impediments in the conventional financial inclusion channels are among these barriers. Nonetheless, these obstacles become less severe as a woman's income rises. Women frequently encounter particular challenges when it comes to digital financial inclusion, including the high cost of mobile financial services, a lack of funds, and restricted access to cellphones. By examining the effect of digital financial inclusion on women's labour force participation in African nations and identifying obstacles to women's digital financial inclusion based on individual-level data, the study adds to the body of existing work. It recommends that in order to boost women's engagement in the labour market, African governments should increase financial inclusion for women through digital channels.